Human capital development and parental investment in India - Orazio P. Attanasio; Costas Meghir; Emily Nix (Yale University, Economic Growth Center, 2015)
In this paper we estimate production functions for cognition and health throughout four stages of childhood from 5-15 years of age using two cohorts of children drawn from the Young Lives Survey for India. The inputs into the production function include parental background, prior child cognition and health and child investments. We allow investments to be endogenous and they depend on local prices and household income, as well as on the exogenous determinants of cognition and health. We find that investments are very important determinants of child cognition and of health at an earlier age. We also find that inputs are complementary and crucially that health is very important in determining cognition. Our paper contributes in understanding how early health outcomes are important in child development.
Keywords: I14; I15; I25; I32; J13; J24; O15; 330; Human Capital; Child Development; India; Intergenerational Transmission; Bildungsinvestition; Eltern; Kognition; Produktionsfunktion; Gesundheit; Kinder; Indien